2017
DOI: 10.4172/2155-9899.1000513
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Anti-Nuclear Antibodies and Obesity is Likely Mediated by Abdominal Adiposity and Systemic Inflammation

Abstract: Background: Obesity and abdominal adiposity have been associated with inflammation as have the presence of anti-nuclear antibodies (ANAs). It was recently reported that there is a decreased likelihood of ANAs in the obese general population. To examine this relationship we used data from adult participants in the National Health and Nutrition and Examination Survey 1999Survey -2004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Under these circumstances, the presence of antinuclear antibodies (ANA) imposes a great challenge as ANA may suggest associated autoimmune liver diseases, however the exam lacks specificity, since even the inflammatory state of metabolic syndrome may favor the occurrence of such antibodies (Blanco, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the presence of antinuclear antibodies (ANA) imposes a great challenge as ANA may suggest associated autoimmune liver diseases, however the exam lacks specificity, since even the inflammatory state of metabolic syndrome may favor the occurrence of such antibodies (Blanco, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found no association between recurrent miscarriage and a positive ANA (80)(81)(82), and others note that the likelihood of miscarriage is not increased with women with a positive ANA (83)(84)(85). Moreover, a tendency to miscarry is associated with factors such as advanced maternal age and obesity (86,87), both of which are known to be associated with a higher prevalence of ANA positivity (88,89). Also, autoimmune thyroid disorders are associated with recurrent miscarriage (69).…”
Section: Treating Rheumatologic Aspects Of Recurrent Pregnancy Lossmentioning
confidence: 99%